PENGISIAN JABATAN KEPALA NEGARA: ANALISA TERHADAP KRITERIA CALON DAN SISTEM PEMILIHAN DALAM PERSPEKTIF ISLAM - Sujatnika, Ghunarsa (Journal of Islamic Law Studies, 2018)
One of the characteristic of Islam in the beginning of glorious era is success in politics. The glorius of Islam continues until the last caliphate, Ottoman Empire. However, there are problems in the elec- tion system of the Head of State. Prophet Muhammad PBUH did not provide example about how to elect and the criteria about whom must be chosen. There are two models of the election. First, with the musyawarah by the ahlul halli wal ‘aqdi, and the second, with the appointment by the previous leader. In that context, some of ulamas like Imam Al Mawardi, Said Hawwa, were in the position to stipulate the criteria about the Head of State, like equitable, faqih, have a clear vision and mission, healthy, not differently-able person, brave, and have a nasab. In Indonesia, maybe it is hard to apply that system, but some of criterias can apply in Indonesia system, indeed. In this case, it is important to apply the values of Islam in Indonesian constitutional system.